(untitled) (Bangladesh Journal of Urology, 2025)
Background: TGBX has recently emerged as a popular technique worldwide with the aid of technological advancements. Compared to SBX, this technique has been shown to provide successful outcomes in numerous studies. In this technique, unlike in SBX, biopsy cores are obtained from the suspicious lesions detected on mpMRI. Objective: To compare the prostate cancer (PCa) detection rate of SBX and TGBX in biopsy naive men in Bangladesh. Methods: This comparative study was done in Department of Urology, Combined Military Hospital (CMH), Dhaka during July 2022 to June 2023. A total of 178 patients of male sex, aged 41-80 years with a PSA level > 4 ng/ml and/or having abnormal DRE findings were included in this study. The data were systematically collected in data collection sheet, were analyzed, tabulated and interpreted subsequently by computer based program IBM SPSS (V. 23). Result: Out of 178 study population, overall CDR was 53.4% (95/178). The yielding rate of total and clinically significant (CS) prostate cancer was better in patients who received mpMRI than in those who did not. The CDR was little higher in the targeted group than in the systematic group (55.81% vs. 48.15% respectively, p > 0.05).There was no statistically significant difference in the detection rate of CS PCa patients between systematic biopsy and targeted biopsy (40.7% vs. 48.8%, respectively, p = 0.732).The CI PCa detection rate was also similar between the two groups (6.98% vs. 7.41%, p> 0.05). Conclusion: Prebiopsy mpMRI with subsequent targeted biopsies for suspicious lesions can yield a higher cancer detection than systematic biopsies. Bangladesh J. Urol. 2024; 27(1): 33-47